The structural changes and recovery times of the knee joint after long distance running of the marathon runners: โครงสร้างข้อเข่าของนักวิ่งมาราธอน - P, Ryden (Biomedical Sciences and Clinical Medicine, 2019)
The influence of long distance running of the knee joint structures and surrounding is still a matter of debate. A few studies with small number of subjects have a conflicting of the results but some of them found the impact of long distance running on the marathon runners and even others runners. The recently report had shown decreased osteoarthritis risk in experienced marathon runners , but some reports have found structural change before and after long distance running. To address this challenges, this article aim to get a better understanding morphology structures and surrounding changes and recovery times on the knee joint of the marathon runners.